Pengenalan Produk Printer 3D sebagai Alternatif Pengolahan Sampah Botol Plastik (PET) di SD Impress 5 Pulau Raam Sorong Kepulauan - Rezza Ruzuqi; Hendra Poltak; Andreas Pujianto; Endang Gunaisah; Handayani Handayani; Ismail Ismail (To Maega : Jurnal Pengabdian Masyarakat, 2023)
The waste problem is endless, especially non-organic waste. Garbage that has been collected and not managed properly can cause big problems. Raam Island is one of the areas in the city of Sorong that is constrained by waste problems. Many non-organic wastes cannot be resolved. It is a challenge for academics to be able to help solve. In this activity, one of the efforts made was the socialization of the existence of a method that can be applied to reduce non-organic waste. One of them is the introduction of 3D printer products processed from polyethylene terephthalate (PET) non-organic plastic waste. Plastic non-organic waste of Polyethylene Terephthalate (PET) is waste produced from drink bottles, such as mineral water bottles. Knowledge of non-organic waste processing techniques needs teaching from an early age. Therefore, socialization activities are carried out starting from the elementary school level. This activity resulted in the additional insight that there is a new method for processing non-organic plastic waste, especially the type of Polyethylene Terephthalate (PET) often used in everyday life. Based on survey results, data was generated that this activity was very beneficial for the surrounding community. It is hoped that after this activity, the surrounding community can start not directly disposing of drink bottle waste but could collect it and then process it into useful products.